Dietary Practices and Influencing Factors of Winneba SHS Students - Linda Cobbah; Ebenezer Appah Bonney (JINAV: Journal of Information and Visualization, 2021)
The study examined the influence of dietary practices on the academic performance of boarding school adolescents. The sample consisted of 264 selected boarding school students from forms one, two and three, respectively. A multistage sampling procedure was adopted in the selection of respondents and structured questionnaire was the main instrument for data collection. The Cronbach’s alpha reliability of the instrument was 0.82. Data were quantitatively analysed using descriptive statistics and presented in the form of tables. The study revealed that consumption of unhealthy snack foods, skipping of meals especially breakfast and low intake of fruits and water were dietary practices which were influenced by several factors with hunger ranking highest. It was concluded that the students engage in poor dietary practices such as skipping of breakfast, and excessive snacking. Recommendations given included; educating the students on the importance of adopting positive dietary practices such as regular breakfast intake and moderate snacking in order to maintain general wellbeing, remain active in class and achieve higher test scores throughout their course period.